EFFECTIVENESS OF HYPNOBREASTFEEDING AND MORINGA LEAF PUDDINGON BREAST MILK PRODUCTION IN PRIMIPARA POST PARTUM AT RSPKT PRIMA SANGATTA - Fatmawati, Zeny; Hartatik, Naning; Suryani, Lilis (Lux Mensana: Journal of Scientific Health, 2023)
Introduction. Indonesia's still-high infant mortality rate is evidence that the Sustainable Development Goals have not been met. Babies in Indonesia are at risk of stunting and death due to a lack of breast milk. The polyphenols, alkaloids, and phytosterols found in moringa leaves, including campesterol, β-sitosterol, and stigmasterol, stimulate the formation of breast milk. Examining the effects of Hypnobreastfeeding and Moringa pudding on milk production is the primary goal of this study. Methods. The study was quasi-experimental and employed a non-control group design with non-equivalent pre-and post-tests. This kind of study employs purposive sampling. Two groups of thirty-two participants were used in the study; one group received hypnobreast feeding and the other received moringa leaf pudding. The selection of participants was based on inclusion and exclusion criteria. Giving Moringa leaf pudding and the hypnobreastfeeding method were the independent factors in this investigation. Primiparous postpartum women's milk production is the dependent variable in this research. A paired T-test is used as the statistical test. Results & Analysis. On the other hand, Both the first and second groups had breast milk production levels between 25 and 150 ml before receiving the hypnobreastfeeding intervention and Moringa leaf pudding; following treatment, these levels rose to above 150 ml. of the paired t-test for both groups showed a p-value of 0.001, where the p-value was <0.05. Discussion. First-time postpartum moms at RSPKT Prima Sangatta who participated in hypnobreastfeeding and received moringa leaf pudding had a statistically significant increase in their milk supply.